2014
DOI: 10.1108/he-11-2013-0062
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers’ resilience and their readiness for building children's resilience

Abstract: Purpose – The purpose of this paper is to analyse the resilience of preschool teachers, aspects of teachers’ readiness to develop children's resilience and the relationship between the two constructs of resilience and readiness. Design/methodology/approach – Two instruments (the “Resilience Scale For Adults” and the “Questionnaire on the Readiness of Preschool Teachers for Developing Children's Resilience”) were used to collect data on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…The same was true for all the self-efficacy subscales where respondents gained mean scores higher than the expected average scores in the subscales. Perception of high resilience among child care providers has already been mentioned by Bouillet, Ivanec and Miljević-Riđički (2014).…”
Section: Levels Of Self-efficacy Self-efficacy Subscales and Resilimentioning
confidence: 99%
See 2 more Smart Citations
“…The same was true for all the self-efficacy subscales where respondents gained mean scores higher than the expected average scores in the subscales. Perception of high resilience among child care providers has already been mentioned by Bouillet, Ivanec and Miljević-Riđički (2014).…”
Section: Levels Of Self-efficacy Self-efficacy Subscales and Resilimentioning
confidence: 99%
“…Considering the multifold function of the CDW and the arduous nature of the child care profession (Levy & Poertner, 2014), exploring DCWs' resilience is substantial in discovering their needs, concerns and professional satisfaction amidst a stressful work environment (Hegney, Rees, Elay, Osseiran-Moisson, & Francis , 2015). In the context of child care profession, a study by Bouillet, Ivanec and Miljević-Riđički (2014), revealed that, at the average, child care professionals, that is, child care educators, rated themselves as having high levels of resilience. The same authors further found that those who perceived being highly resilient also evaluated themselves as capable of fostering resilience among children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the multifold function of the CDW and the arduous nature of the child care profession (Levy & Poertner, 2014), exploring DCWs' resilience is substantial in discovering their needs, concerns and professional satisfaction amidst a stressful work environment (Hegney, Rees, Elay, Osseiran-Moisson, & Francis , 2015). In the context of child care profession, a study by Bouillet, Ivanec and Miljević-Riđički (2014), revealed that, at the average, child care professionals, that is, child care educators, rated themselves as having high levels of resilience. The same authors further found that those who perceived being highly resilient also evaluated themselves as capable of fostering resilience among children.…”
Section: Introductionmentioning
confidence: 99%
“…Los individuos que poseen y ponen en práctica este tipo de habilidades, obteniendo un aprendizaje y desarrollo positivo a través de situaciones consideradas desestabilizantes, son aquellos que poseen lo que comúnmente se llama un "perfil resiliente" (Kim y Lee, 2018). La resiliencia está definida como la capacidad de superar situaciones adversas, independientemente del grado de gravedad con el que las percibe cada individuo, que permite salir de ellas fortalecido y de manera airosa (Bouillet, Ivanec y Miljević, 2014;Campos y González, 2018;Rincón, 2016;Rodríguez, Ramos, Martínez y Rey, 2018). Las personas resilientes son capaces de tomar situaciones consideradas perjudiciales como una base para el crecimiento personal y el autoaprendizaje (Richards, Levesque, Templin y Graber 2016).…”
unclassified